Pengembangan Teknologi E-Commerce dengan Menerapkan Metode CRM dan Forecasting - Norman Norman; Depi Rusda (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The development of e-commerce technology is a sales process that is carried out online which can make it easier to sell without having to come to the store directly. Dalwa Zain Collection store which is a clothing store that sells Muslim and Muslim clothing for men and women. This e-commerce sales system will be applied to the Dalwa Zain Collection store to make it easier for shop owners to make transactions and also make it easier for consumers at the purchase stage without having to go to the shop. In this e-commerce system, there are two methods, namely to apply the forecasting method to carry out the annual forecasting stage at the Dalwa Zain Collection store and to apply the CRM (Customer Relationship Management) method as the application of discounts on clothing in the Dalwa Zain Collection store. This is the stage of the process that will be carried out so that the Dalwa Zain Collection store can see its sales from year to year and also make the discount that will be set can be helped to overcome quickly.